Psicanálise e docência no ensino superior: desejo e discurso - Silveira, Juliana Freitas da (2019)
This dissertation presents a look at the link between education and psychoanalysis, more specifically, the university lecturer, a theme that arises from some concerns that were provoked in me through the academic, professional and scientific path by entering the PEG - Special Program of undergraduate in Teacher Training for Vocational Education. The objective of this master's research is to problematize the discourse present in the choice of teaching in higher education and the desire to exercise it, as well as to analyze the social ties / discourses in face of the implications in the referred teaching practice. To achieve the objectives, a research in psychoanalysis was carried out, which is linked to the chosen theoretical framework and the assumptions of all psychoanalytic work. Such assumptions are thus understood by enabling and allowing access to the word through listening, transfer and free association. The three participants in this study are linked to the humanities area and are thus: in doctoral stage; in the exercise of teaching in early career; in the exercise of teaching at the end of career. As a result of this research and as a result to achieve the objectives, two articles were developed - to be described below. In the first, I will present the unique path of each teacher interviewed and the thinking about the desire to exercise university teaching in each participant. In order to problematize the desire to practice teaching in higher education together with thinking about the social bond at each moment of this path and its link with education, the first article was titled as “University teaching and the desire to exercise it: listening at different times of this route ”. The second article, “The circulation of discourses in the exercise of university teaching: the transposition of the place of the teacher”, in turn, aims to present the discourses in Lacanian theory, as well as to analyze the discourses present in the teaching practice. In this process of listening and writing, I chose to do a case analysis in psychoanalysis of the early career teacher, since it presented a discourse more open to misunderstanding and a possibility of discursive circulation that will transpose the master's discourse. The reflection that I was able to construct throughout this dissertation allows me to think of university teaching as a profession that meets the other: either by thinking of the desire that boldly attributes the constitution of being a teacher, or the discourses presented in the Lacanian field, where I approached the importance of circulation for the non-illness of the university lecturer, the approach / the meeting teacher-student. In its elaboration, I allowed myself the following gesture: to try to transform academic writing, displacing it from the university discourse, which meets the purpose of this study: to make sense in / by the field of metaphor, poetry and polysemy of words. that made their marks here.